2020
DOI: 10.1080/03014460.2020.1717615
|View full text |Cite
|
Sign up to set email alerts
|

Tanner’s tempo of growth in adolescence: recent SITAR insights with the Harpenden Growth Study and ALSPAC

Abstract: Background: James Tanner emphasised the "tempo" of growth, i.e. the adolescent spurt as summarised by its timing (age at peak velocity or APV) and intensity (peak velocity, PV). Aim: The paper applies the SITAR growth curve model to pubertal growth data with the aim of clarifying the growth pattern across multiple measurements and the spectrum of APV and PV. Subjects and methods: Data for 7-20 years on ten anthropometric measurements in 619 children from the Harpenden Growth Study, and on height in 10410 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Linear growth velocity in late childhood gradually decreases to a nadir and then rises to a peak velocity of about 10 cm/year for boys and 8 cm/year for girls. The mean take‐off age in boys is about 11.5 years, 2 coinciding with the mean age at Tanner stage 2 (11.6 + ‐0.09) 17 . As our cohort included only prepubertal boys, aged 10–14.5 years at baseline, the older participants would be expected to have, and indeed did demonstrate, a negative Δ height‐SDS during the study period.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Linear growth velocity in late childhood gradually decreases to a nadir and then rises to a peak velocity of about 10 cm/year for boys and 8 cm/year for girls. The mean take‐off age in boys is about 11.5 years, 2 coinciding with the mean age at Tanner stage 2 (11.6 + ‐0.09) 17 . As our cohort included only prepubertal boys, aged 10–14.5 years at baseline, the older participants would be expected to have, and indeed did demonstrate, a negative Δ height‐SDS during the study period.…”
Section: Discussionmentioning
confidence: 78%
“…Even fewer studies have attempted to improve growth by nutritional interventions in later stages of childhood or adolescence, 12,13 compared to earlier stages in childhood. This is perhaps due to the challenge of evaluating nutritional interventions in a period in life with such large variability in growth tempo 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…To assess growth velocity in non-ACH children the Harpenden Growth Study (Tanner et al 1976) provides a useful reference, the data having recently been reanalysed using SITAR (Cole 2020). The Harpenden study consisted of 248 girls and 371 boys recruited from a children's home in Harpenden England between 1949 and 1969, with regular measurements of height, sitting height and leg length (by difference) from 7 to 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…In non-ACH children there is a marked growth spurt in height during puberty, when mean height velocity reaches 8-10 cm/year at its peak (Cole 2020). Analysing the data cross-sectionally, children with ACH appear not to have a pubertal height growth spurt.…”
Section: Introductionmentioning
confidence: 91%
“…One plausible explanation for such results may be linked to differences in the timing and tempo of the growth spurt. This growth period is marked by an asynchrony in the growth of different parts of the body 25,26 that can adversely affect motor control, a phenomenon termed "clumsiness" or ''adolescent awkwardness'' 27 . For example, Bisi and Stagni 28 in an experimental study compared the gait performance of growing (height increase > 3 cm in 3 months) and not growing (height increase < 1 cm in 3 months) male adolescents during a walking task and showed that the growth spurt in uenced gait variability, smoothness and regularity.…”
Section: Discussionmentioning
confidence: 99%